Meaning of Discretion Over Government Legal Actions in Public Policy - Ujang Charda (Journal of Law Science, 2024)
The state has a goal of realizing prosperity for its people (welfare state), so the state needs to implement public policies in the context of the quality of public services which are influenced by internal factors, namely discretionary authority. The research method used is analytical descriptive with a normative juridical approach through library and field research stages with data collection techniques through library studies Based on the research results, show that discretion can be used by government officials to penetrate the legality of legal products which sometimes encounter deadlock, as long as it is in the interests of the people at large, so there is no reason for government officials to refuse to adopt a policy. If the law or other legal products do not regulate it formally, it does not mean that the situation will close the space to provide happiness for the people, the freedom to act is in the hands of government officials